Throughput and Delay Analysis of IEEE 802.11-Based Tree-Topology Networks - Kanematsu, Takeshi; Wan, Yin; Sanada, Kosuke; Li, Zhetao; Pei, Tingrui; Choi, Young June; Nguyen, Kien; Sekiya, Hiroo (IEEE Open Journal of the Communications Society, 2020)
This article aims to investigate the performance of the IEEE 802.11-based tree-topology network, where a wireless node is within the others' carrier sensing ranges. In such a network, the concurrent transmission is a dominant cause of frame collisions. Moreover, the relay nodes (RN) (i.e., in the tree) likely cause the coexistence of non-saturated and saturated nodes in the networks. Those conditions have not been addressed in the previous works yet. As a solution, this work proposes new analytical expressions of delay and throughput in the investigated scenario. The presented analytical model incorporates the Bianchi model and airtime concept to formulate operations of the IEEE 802.11 nodes. First, by leveraging Bianchi-based analysis, the proposed model gives the frame collision probability caused by concurrent transmission. Second, by using airtime concept analysis, the ratio of frame numbers of each flow in a relay node (RN) is expressed to represent the buffer state of RN. As a result, we can obtain the network throughput, the throughput, and the delay of each flow. The validity of the analytical expressions is confirmed by the quantitative agreement between the analytical and simulation results.
Keywords: Analytical expressions; Carrier sensing; Collision probability; Concept analysis; Concurrent transmission; Delay analysis; Network throughput; Quantitative agreement; airtime; Bianchi; delay; performance analysis; throughput; Tree topology